Analysis of green chemistry content in form IV and V high school chemistry textbooks in Malaysia - Aura Heidya Septa; Antuni Wiyarsi (Universitas Negeri Yogyakarta, 2025)
Malaysia is one of the countries that has integrated the STEM (Science, Technology, Engineering, and Mathematics) approach in its education curriculum since 2017, to prepare young people with 21st century skills. In the context of chemistry education, Malaysia also applies the concept of Green Chemistry to encourage environmental awareness and improve science literacy through materials relevant to global sustainability issues. This study examines the integration of Green Chemistry principles in Level IV and V high school chemistry textbooks in Malaysia. Utilizing a qualitative descriptive content analysis, the study focuses on six themes: Green Chemistry principles, application fields, presentation stages, presentation levels, locality aspects, and related chemistry concepts. Analysis of the textbooks revealed that seven out of twelve Green Chemistry principles are integrated, with